Coffee - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Clarke, R.J. and R Macrae (eds.). 1985. Coffee. Volume 4 - Agronomy, Elsevier Applied Science. London and New York ISBN 1 85166 132 8